The Influence Pengaruh Player Satisfaction, Virtual Item Value, Dan Collaboration Branding Terhadap Purchase Intention Gacha Pada Game Jepang “Pigg Party - Rini Susilawati; Khumairah, Dean Zahra; Nawarcono, Winanto; Untara, Untara (Sekolah Tinggi Ilmu Ekonomi SBI, 2025)
ABSTRACT The purpose of this study is to examine the effect of Player Satisfaction, Virtual Item Value, and Collaboration Branding of PIGG PARTY gacha. Gacha in free-to-play games can be done with free game coins/tickets and obtained normal to rare items that can be done by purchasing game coins with real money. This study used primary data collected from respondents who were PIGG PARTY players with the minimum age of 17 years old and had been purchasing gacha. The respondent were approached through PIGG PARTY Facebook group, Discord, WhatsApp and in PIGG PARTY game who were given the link to the online questionnaire set in google form which provided 100 data. The technique for analyzing data was Structural Equation Modeling - Partial Least Square (SEM-PLS) using the SmartPLS 3.0 application. With the results of this study explained that: 1) Player Satisfaction has a possitively affects on Purchase Intention, 2) Virtual Item Value significantly and positively affects on Purchase Intention, 3) Collaboration Branding has a significantly positive. Keywords: satisfaction player, virtual item value, Collaboration Branding, purchase intention